Cardiomyopathy as the forgotten symptom of systemic lupus erythematosus in children: A case report - Yudhianto, Eric; Malisie, Ririe F.; Abdillah, Hafaz Z.; Rusli, Rita E. (Narra J, 2025)
Cardiomyopathy is a rare clinical manifestation in pediatric systemic lupus erythematosus (SLE), with only a single case reported in the literature. Its identification in pediatric SLE is challenging due to its typically subclinical presentation and low incidence, which frequently result in delayed diagnosis and management. The aim of this study was to present a unique case of dilated cardiomyopathy, a rare cardiac complication of SLE, which can be life-threatening if not promptly recognized and treated. An 11-year-old boy was admitted to the emergency department of Murni Teguh Memorial Hospital, diagnosed with SLE based on the 2019 European Alliance of Associations for Rheumatology (EULAR) criteria, with a total score of 30 and a Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score of 16, indicating high disease activity. Clinical findings included oral ulcers, a non-pruritic hyperpigmented discoid macule, anemia, lymphopenia, positive both the direct and indirect Coombs tests, elevated D-dimer level, and pulmonary congestion. Initial treatment stabilized the patient condition, allowing transfer to the general ward by day five. Five days after admission, the patient developed palpitations and tachycardia, with a heart rate of 140 beats per minute. Electrocardiography showed sinus tachycardia, while echocardiography revealed all cardiac chambers dilation, left ventricular ejection fraction (LVEF) of 43%, moderate mitral regurgitation, and mild pulmonary regurgitation, subsequently diagnosed as dilated cardiomyopathy. Heart failure therapy was initiated with intravenous furosemide, oral ramipril, and digoxin. Palpitations and tachycardia resolved within two days. Following two weeks of treatment, the patient was discharged with stable vital signs. A one-month follow-up thoracic echocardiography demonstrated improved cardiomyopathy, with an LVEF of 53%. Cardiomyopathy in pediatric SLE is rare but can cause significant morbidity and mortality if undiagnosed. Its nonspecific presentation and immune-mediated pathogenesis make early detection challenging. Due to its rarity, it may be overlooked, highlighting the importance of comprehensive cardiac evaluation, including echocardiography, in children with suspected cardiac involvement.